Mitigating Financial Statement Fraud Perpetrated by Corporate Psychopaths - Busila, Angela (Journal of Accounting and Finance, 2024)
This paper proposes a fraud mitigation model that focuses on corporate psychopathy's impact on material misstatement of financial statements fraud. Prior research on psychopathy and corporate psychopaths has found that people with these tendencies do not possess the need to rationalize their behavior, therefore negating the rationalization point present in most prior fraud theory models. There is ample prior research on the impact of corporate psychopaths’ effect on corporate culture. There is also an abundance of prior research on fraud theory and how fraud is perpetrated. Drawing from existing research in these areas, this proposed fraud mitigation model identifies and addresses the elements present when corporate psychopaths perpetrate fraud. Board of directors will benefit from this study when they unknowingly hire leaders who exhibit corporate psychopathic traits that can impact financial reporting and internal controls procedures. Other stakeholders and the public interest may benefit from lower risk of financial statement fraud due to fewer corporate psychopaths in leadership positions perpetrating financial statement fraud.